2011
DOI: 10.1656/058.010.0210
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Oil and Gas Development on Wintering Grassland Birds at Padre Island National Seashore, Texas

Abstract: , I surveyed 5 active, 4 abandoned, and 4 road sites to investigate the relationship between distance from disturbance (well pads, access roads) and bird abundance. I also compared abundance among the 3 site types. At each site I recorded bird numbers and species in 10-m distance bands along all transects (4 transects/well, 2 transects/road), each extending 300 m from the road or pad.At road sites bird abundance was positively correlated with increased distance from road edge, but I found no linear relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Alternatively, aboveground infrastructure associated with shallow gas wells in our study area may provide novel visual cues that are interpreted by songbirds as potential perch sites. Our results are consistent with this hypothesis; wells attracted species such as vesper sparrow (Jones and Cornely ) and western meadowlark (Lawson et al ) that vocalize and display from perches. Species that do not tend to use perches and avoid shrubs, such as Sprague's pipit (Robbins and Dale , Grant et al ) and horned lark (Beason ), showed a negative response to shallow gas wells.…”
Section: Discussionsupporting
confidence: 91%
“…Alternatively, aboveground infrastructure associated with shallow gas wells in our study area may provide novel visual cues that are interpreted by songbirds as potential perch sites. Our results are consistent with this hypothesis; wells attracted species such as vesper sparrow (Jones and Cornely ) and western meadowlark (Lawson et al ) that vocalize and display from perches. Species that do not tend to use perches and avoid shrubs, such as Sprague's pipit (Robbins and Dale , Grant et al ) and horned lark (Beason ), showed a negative response to shallow gas wells.…”
Section: Discussionsupporting
confidence: 91%
“…Changes in vegetation structure alone cannot account for these relationships because 1) we accounted for vegetation structure in our models, 2) vegetative cover increased with increasing distance from gas wells in the northern site but not the southern site, and 3) anthropogenic disturbance of vegetation was typically confined to within 10–15 m from gas wells, whereas changes in abundance occurred over larger distances. Therefore, birds may be avoiding some specific feature of the gas wells that we did not quantify, such as vehicular activity (Ingelfinger and Anderson , Lawson et al ); predator abundance (Webb et al ); or avoidance of noise (Blickley et al ), pollutants, toxicants, and invasive species associated with anthropogenic activity (Koper et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Both species are less likely to occur near roads (Sutter et al ) and Dale et al () found Baird's sparrow abundance to be negatively correlated with well density and Sprague's pipit weakly so. Inconsistent results among studies examining the influence of natural gas development on grassland birds may be due to variation in infrastructure age, spatial configuration of development and drilling infrastructure presence (Gilbert and Chalfoun ), chronic industrial noise (Blickley et al ), landscape context (Hamilton et al ), vehicular traffic (Ingelfinger and Anderson , Lawson et al ), regional variation in bird population density (Winter et al ), and pollutants (e.g., toxicants and pesticides; Koper et al , Mineau and Whiteside ). Furthermore, variation in study design and statistical analyses may contribute to inconsistent conclusions among studies.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of the effect of energy infrastructure on the abundance of grassland birds in the oil fields of San Padre Island in Texas, Lawson et al (2011) investigated mean abundance of several bird species along linear transects emanating outward from active oil wells, inactive oil wells, and access roads. The bird species studied included seven that occur in North Dakota: western meadowlark (Sturnella neglecta), savannah sparrow, grasshopper sparrow (Ammodramus savannarum), sedge wren (Cistothorus platensis), Le Conte's sparrow (Ammodramus leconteii), American pipit (Anthus rubescens), and yellow-rumped warbler (Setophaga coronata).…”
Section: Songbirdsmentioning
confidence: 99%